Implementing Precaution in the Legal Framework for Seabed Mining in the Arctic - Duggmo, Svein (UiT Norges arktiske universitet, 2021)
The object of this thesis is to examine and assess how a precautionary approach has been incorporated and implemented in the legal regimes for seabed mining in the Area and on the Norwegian continental shelf in an Arctic context.